Efektivitas Model Pembelajaran Three Minutes Review (TMR) Berbantuan Flipbook Dilengkapi LKPD Interaktif Liveworksheets Terhadap Hasil Belajar Siswa SMA N 2 Waingapu: (Effectiveness of the Three Minutes Review (TMR) Learning Model Assisted by Flipbook Equipped with Liveworkhseets Interactive LKPD on Student Learning Outcomes SMA N 2 Waingapu) - Dimu, Mia Fransiska; Tamu Ina, Anita; Makatita, Audrey Louise (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2024)
The purpose of this study was to determine how the effect of the TMR model assisted by flipbook and liveworksheets LKPD liveworksheets on student learning outcomes at SMA Negeri 2 Waingapu. Student learning outcomes are low because the teacher has never tried to vary never tried to vary other learning models and media used during the learning process used during the learning process. This research is a quantitative research with an experimental approach and random sampling. Samples used in this study were used in this study were class XI IPA 1 as the experimental class, totaling 33 people and class XI IPA 3 as the control class, totaling 33 people. Which amounted to 33 people and class XI IPA 3 as a control class which amounted to 67 people. 34 total sample size of 67 people. The results of the research average pretest score the control class was 49.09 and the average posttest score was 66.66. While for the experimental class the average pretest score was 59.11 and the average posttest score was 72.35. posttest score is 72.35. With an asym sig (2-tailed) value of 0.001 <0.05, the hypothesis test shows that the TMR learning model that is used in the experimental class is more effective than the control class. Hypothesis test shows that the TMR learning model assisted by the flipbook and LKPD liveworkshseets have an effect on student learning outcomes students. Abstrak. Tujuan penelitian ini adalah untuk mengevaluasi bagaimana model TMR yang dibantu oleh mdeia flipbook dan LKPD liveworkhseets berpengaruh pada hasil belajar siswa di SMA Negeri 2 Waingapu. Hal ini disebabkan karena guru tidak pernah mencoba memvariasikan model pembelajaran lain serta media, yang berdampak pada hasil belajar siswa yang rendah. Penelitian ini merupakan kuantitatif dengan pendekatan eksperimen dan pengambilan sampel secara acak. Kelas XI IPA 1 dan XI IPA 3 berfungsi sebagai kelas eksperimen dan kontrol. Hasil menunjukkan nilai pretest dan postest untuk kelas eksperimen 59,11 dan 72,35, sementara nilai kelas kontrol 49,09 dan 66,66. Dengan nilai asym sig. (2-tailed) 0,001<0,05, uji hipotesis menunjukkan bahwa model pembelajaran TMR yang dibantu flipbook dan loveworkhseets LKPD memengaruhi hasil belajar.